A semiotic analysis of colors as the symbol of music genre in the movie Trolls World Tour - Vina Aryanti Aryanti; Merry Rullyanti; Dhanu Ario Putra (Universitas Pakuan, 2025)
This research discusses the semiotics of color as a symbol of genre music on the characters of the film Trolls World Tour. This research has two objectives. (1) To find the colors of the six characters. (2) To analyze the semiotics of colors on the characters connected to the music genre in the film Trolls World Tour. This research looks for Denotative, Connotative, and Mythical meanings. This research uses a qualitative descriptive method. This is related to the description of data in the form of character images from pieces of movie scenes. The analysis in this study uses semiotic analysis from Roland Barthes. Using Karen Haller's color psychology theory and based on research entitled Associating Colors with Musical Genres and Color, Music, and Emotion: Bach to the Blues. The results of this study found 6 Denotative meanings, 6 Conotative meanings, and 2 Myth meanings. The research findings show that 3 out of 6 characters have colors that are connected to music genre.